STUDENT-TEACHERS’ BELIEFS AND PRACTICES OF THE QUESTIONING TECHNIQUES - Lê, Quỳnh Hoa (2021)
Despite being of crucial importance (Thompson, 1996; Brook, 2006), questioning techniques are paid inadequate attention to in many teacher education training courses (Darn and Izmir, 2010). Hence, student-teachers are probably hardly guided in forming reasonable beliefs about questioning techniques and in translating their beliefs into practices. In the meantime, as claimed by Howitz (1985 cited in Canh 2011), “a systematic assessment of the beliefs held by pre-service teachers should be the first step in their development as foreign language teachers” (p. 333). Seeing the lack of formal training in these critical techniques and the significance of understanding preservice teachers‟ beliefs in their novice practices, the researcher sets out to investigate student-teachers‟ beliefs in correlation with their practices of questioning techniques. The study is conducted during the participants‟ 2012 practicum at the Faculty of English Language Teacher Education, University of Languages and International Studies, Vietnam National University, Hanoi, when they have their first formal teaching practice in the real classroom. By completing the study, the researcher also attempts to bridge the gap in the existing literature about the subject matter. The findings of the study show that student teachers‟ beliefs are both similar and dissimilar to their practices, while their practices do not always conform to the recommendations in the literature. From the findings, the study suggests a number of possible reasons for this correspondence and offers implications for both student-teachers and supervisor teachers regarding the subject matter